Good Governance on Village Fund Management with The Use of Information Technology as A Moderating Variable - Safrizal Safrizal; Taufeni Taufik; Yesi Mutia Basri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study contains testing and analysis of the effect of good governance principles on the management of village funds, as well as the use of information technology as moderation. The population in this study was 197 villages in Indragiri Hilir Regency with a sample of 132 villages. The sampling technique used was proportional stratified random sampling based on the village index. The data were analyzed using SPSS. The finding showed all influential hypotheses, namely good governance with the principles of transparency, accountability, and community participation in the management of village funds, and moderated by the use of information technology.